Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Di Pasar Los Batu Kabupaten Hulu Sungai Selatan - Nasiruddin; Fahrati, Eny (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This research aims to know and explain the factors that influence the income of traders in Los Batu Market. The approach used in this research is descriptive quantitative. Total population: 307 people. This study took a sample of 38 people born using the Proportionate Stratified Random Sampling technique. Questionnaires and interviews were used for data collection techniques. The variables in this study are business capital (X1), education (X2), length of business (X3), working hours (X4), and traders' income (Y). Data analysis in this study used multiple linear regression (OLS), with a significance level of 5%. The results show that the variable that partially affects the income of Los Batu Market traders is venture capital (X1). In contrast, the variable level of education (X2), length of business (X3), and working hours (X4) do not significantly affect the income of market traders. Los Batu. Furthermore, the variables of business capital, education, length of business, and working hours greatly influence the income of Los Batu Market traders.